Excess Free Volume and Intermolecular Interaction in Binary Liquid Mixtures of o-Xylene with 1-Alkanols - K. Gupta, Mahesh; Sharma, P.K.; Lagarakha, Rekha; K. Sharma, Dhirendra; Shrivastava, S.N. (Asian Journal of Chemistry, 2010)
The free volume for the three binary liquid systems, o-xylene + 1-propanol, o-xylene + 1-butanol and o-xylene + 1-pentanol, have been studied using density and sound velocity data at 303.15 K. In the present study, a new approach is applied in the computation of internal pressure (P1), which in turn has been used to calculate free volume. The intermolecular interaction in the binary liquid mixtures under consideration has been discussed in the light of excess free volume. The results are consistent with the theories.